"Be sweet to babies": Use of Facebook as a method of knowledge dissemination and data collection in the reduction of neonatal pain. Issue 3 (2nd May 2020) - Vieira, Ana Claudia G.; Bueno, Mariana; Harrison, Denise
Abstract: The Be Sweet to Babies video demonstrates the analgesic effects of breastfeeding, skin‐to‐skin care, and sweet‐tasting solutions as interventions to reduce pain during blood sampling in newborns. Although effective and safe, these strategies are implemented inconsistently in clinical settings. Given the increasing popularity of social media, there is a potential to disseminate and promote health information through it. The study aim was to evaluate the use of Facebook as a means of disseminating the Be Sweet to Babies video in Portuguese, and to evaluate respondents' prior knowledge, previous use of the three pain management strategies and intent to use the strategies in the future. We conducted a cross‐sectional study, using the "virtual snowball" sampling method. A Facebook webpage was created, in which the video was posted along with a brief survey. Data analyzed included number of views and visits to the page, number of views of the video, likes, dislikes, and survey responses. One year after posting, the page had 70 753 views and 2199 accesses; there were 1553 "likes", no dislikes, and 43 positive comments. The survey was completed by 930 respondents (42% response rate based on the page access). Over two thirds of the respondents had previous knowledge about breastfeeding, skin‐to‐skin care, and sweet solutions for pain relief. After watching the video, 87% of the respondents intended to use breastfeeding or skin‐to‐skin care in the future, and 71% intended to use sweet solutions. Almost all viewers rated the video as very useful (n = 917, 99%), easy to understand (n = 926, 99%), and easy to apply in real‐life situations (n = 903, 97%). Using Facebook to deliver and evaluate an intervention is feasible, rapid in obtaining responses, low cost, and it is promising for data collection and knowledge dissemination. Further studies are warranted to evaluate the actual impact of the use of social media in practice change.